Malpractice in surgery : safety culture and quality management in the hospital - Imhof, Michael, 1951- (Patient safety ;, 2013)
The intensive care units record 1.7 medical errors per patient and day. The most affected disciplines are the operative disciplines, particularly surgery. Medical errors mainly occur when the indication for surgery is being made, during surgery and post-surgery. Suspicious oncological diagnostic results and post-operative complications are also often ignored. This book deals with typical medical errors in surgery. It shows solutions and ways of dealing effectively with these errors and how to establish an efficient security management system.